THE RELATIONSHIP POVERTY AND ECONOMIC DEVELOPMENT - Salma, Nur; Akhdzulhijah, Sri Ayadilah; Maharani, Intan (LPPM Universitas Bina Bangsa, 2024)
Economic growth and poverty are important processes that determine the success of a country. Each country continues to try to achieve good economic growth and reduce poverty. Of the many countries in the world, the first requirement for reducing poverty is economic growth. However, the state of developing countries including Indonesia, successful economic growth must be accompanied by the emergence of difficulties in increasing the population living below the poverty line. Development is a must for a country if it wants to improve the standard of living and welfare of its people. Development is carried out through various efforts, both sectoral and regional. Development is not the goal of a country, but development is one way to increase the economic growth of a country. High economic growth if not followed by equitable development in all groups of society, then the country's goals will not be achieved.